Effects of Quercetin and Resveratrol on in vitro Properties Related to the Functionality of Potentially Probiotic Lactobacillus Strains - dos Santos, Aldeir Sabino; de Albuquerque, Thatyane Mariano Rodrigues; de Brito Alves, José Luiz; de Souza, Evandro Leite (Frontiers in Microbiology, 2019)
The ability of probiotics to exert benefits on host has been associated with different physiological functionalities in these microorganisms, namely cell surface hydrophobicity, autoaggregation, coaggregation with pathogens, antagonistic activity against pathogens and ability to survive the exposure to gastrointestinal conditions. This study assessed the effects of different concentrations of quercetin (QUE) and resveratrol (RES) on the ability of six potentially probiotic Lactobacillus strains to tolerate different pH values and bile salt concentrations, to autoaggregate, coaggregate with and antagonize pathogens and survive the exposure to simulated gastrointestinal conditions. QUE and RES presented low inhibitory effects on all tested Lactobacillus strains, with minimum inhibitory concentration (MIC) ranging from 512 to >1024 μg/mL. In most cases, QUE and RES at all tested concentrations (i.e., MIC, 1/2 MIC and 1/4 MIC) did not affect the tolerance of the Lactobacillus strains to acidic pH and bile salts. QUE increased cell surface hydrophobicity of most of the tested Lactobacillus strains and increases or decreases in cell surface hydrophobicity varied in the presence of different RES concentrations among some strains. QUE and RES increased the ability of tested Lactobacillus strains to autoaggregate and coaggregate with pathogens. QUE and RES did not negatively affect the antagonistic activity of the tested Lactobacillus strains against pathogens and did not decrease their survival rates when exposed to in vitro gastrointestinal conditions. In a few cases, the ability of some tested Lactobacillus strains to antagonize pathogens, as well as to survive specific steps of the in vitro digestion was increased by QUE and RES. QUE exerted overall better protective effects on the measured in vitro properties of tested Lactobacillus strains than RES, and L. fermentum and L. plantarum strains presented better responses when treated with QUE or RES. These results showed that probiotic Lactobacillus strains could present low susceptibility to QUE and RES. Combined use of QUE and RES with probiotic Lactobacillus could improve their functionalities on the host; however, the concentration of these polyphenols should be carefully selected to achieve the desirable effects and vary according to the selected probiotic strain.